PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENCURIAN DALAM KELUARGA (ANALISIS KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 760 K/PID/2013) - Gunawan Sinurat; Alvi Syahrin; Mahmud Mulyadi; Edi Yunara (Universitas Sumatera Utara, 2017)
ABSTRACT Law is a tool in protecting the rights of people whose purpose is order and tranquility in society, but the law alone will not be able to achieve that goal. Nowadays the frequent complaints in the police are the cases of the family has increased, because the current society assumes that any problems will be better resolved with the domain of the court when it would be nice if resolved by way of kinship. The provision of Article 367 of the KUHP can be seen that the theft in the family is a complaint offense, meaning that there is or not a claim against this offense depends on the agreement of the disadvantaged / victims / people determined by law. Keywords: Theft and In The Family.